Diversity and Uses of Medicinal Plants in Panama [Diversidad y Usos de Las Plantas Medicinales en Panamá] - Martinez-Salinas, J; Morales-Munoz, B (Universidad de Santiago de Chile, 2019)
Panama has 10,444 species of plants, some with medicinal properties, but there is no inventory to determine the totality of medicinal plants that are used. Our goal is to perform a review of publications and research with a view to presenting an estimated on the diversity of medicinal species and types of uses. Throughout the country are used medicinal plants, but its use is increasing more rural areas, and this is due to the scarcity of health services. The species most sold in pharmacies and public markets are: Equisetum bogotense (cola de caballo), Lippia alba (tilo), Pluchea carolinensis (salvia), Cymbopogon citratus (hierba de limón), Neurolaena lobata (contragavilana), Costus spicatus (caña agria) and Momordica charantia (balsamino). Among some species of medicinal plants that are exported we have: Psychotria ipecacuana (raicilla), Smilax aspera (zarzaparrilla) and Ficus benjamina. © 2019, Universidad de Santiago de Chile. All rights reserved.